The Envelope (E) Protein of SARS-CoV-2 as a Pharmacological Target - Teresa Santos-Mendoza (Viruses, 2023)
The COVID-19 pandemic caused by the SARS-CoV-2 virus is still a global health concern. Several spike (S) protein-based vaccines have been developed that efficiently protect the human population against severe forms of COVID-19. However, some SARS-CoV-2 variants of concern (VOCs) have emerged that evade the protective effect of vaccine-induced antibodies. Therefore, efficient and specific antiviral treatments to control COVID-19 are indispensable. To date, two drugs have been approved for mild COVID-19 treatment; nevertheless, more drugs, preferably broad-spectrum and ready-to-use therapeutic agents for new pandemics, are needed. Here, I discuss the PDZ-dependent protein-protein interactions of the viral E protein with host proteins as attractive alternatives for the development of antivirals against coronavirus.